REGARDING BURIAL STRUCTURES IN KOVARDON - Dilmurod Normurodov (Journal of Social Sciences and Humanities Research Fundamentals, 2023)
In this article, the burial structures found in the village of Kovardon, Urochi Chirchik district, Tashkent region, are analyzed. It is recorded that the deceased were laid on the ground in the graves, and the bones of the deceased, cleaned of flesh, were buried in the graves. Based on the analyzed graves and the artifacts found in them, it is correct that the Qovunchi culture dates back to the 2nd to 1st half of the 6th century AD, and that the inhabitants of the Tashkent oasis underwent changes in the tradition of burying the dead in the 7th-7th centuries. given ‎